In the Circle of the Jewish Question and the Muslim Question or How Muslims Turned into Placeholders for “The Jew” in German Public Discourse - Asher J. Mattern (Religions)
This article examines the interplay between Jewish and Muslim identities in German public discourse, focusing on their roles as placeholders in constructing contemporary German identity. It argues that discussions of Judaism, antisemitism, and the Israel–Palestine conflict often serve as projection surfaces for national self-perception, neglecting the complexities of Jewish and Muslim lived realities. Drawing on critiques by Elad Lapidot and Jean-Claude Milner, the article explores how the exclusion of heteronomous identities—grounded in divine law—exposes the structural limitations of modern liberal societies. It highlights the substitution of traditional Jewish identity with a liberal-compatible version in German discourse, while simultaneously framing Muslims as the “new Other”. This text calls for Jewish and Muslim communities to challenge the narratives that marginalize and instrumentalize them, advocating for solidarity to address shared challenges and enrich pluralistic democratic frameworks.